Biodegradation behavior and tribological properties of ultrahigh molecular weight polyethylene stabilized with α-tocopherol. Issue 3 (29th March 2019) - Kang, Xueqin; Yao, Chi; Ge, Shirong
Abstract : Purpose: This paper aims to investigate the effect of simulated body fluid (SBF) on biodegradation and tribological properties of ultrahigh molecular weight polyethylene (UHMWPE) and UHMWPE stabilized with α-tocopherol. Design/methodology/approach: The samples of UHMWPE and UHMWPE stabilized with α-tocopherol were prepared by a hot-pressing method, and then immersed in SBF for one year. Tribological test was performed on a UMT-2 tribometer. Findings: The crystallinity and tribological properties increased slightly after UHMWPE stabilized with α-tocopherol, whereas the O/C ration decreased slightly. The crystallinity and O/C ratio increased after all samples immersed in SBF for one year. This resulted in the deterioration of tribological properties and the wear mechanism change. The tribological properties change was smaller in UHMWPE stabilized with α-tocopherol than that in UHMWPE, because the oxidation resistance of UHMWPE was increased by α-tocopherol. Originality/value: The results of the experimental studies demonstrated and compared the biodegradation behavior and tribological properties of UHMWPE, UHMWPE stabilized with α-tocopherol, and after they immersed in SBF for one year.